An Investigation of Multilingual Domestic University Student Perceptions of English for Academic Purposes - Wenjin Vikki Bo; Lyndon Lim; Yuna Lin (Behavioral Sciences, 2022)
It is well-established that English for academic purposes (EAP) programmes are critical for academic success in English-medium universities. Nonetheless, there is significantly less research on how EAP programmes impact multilingual domestic university students, compared to that of international students who speak English as a foreign language. While an earlier study on a university in Singapore found that an EAP programme had a statistically significant and positive intervention effect on students’ grade point average of the first semester upon matriculation, this study sought to investigate the perceptions of students from the same university, as this would contribute to how EAP programmes could be refined to better support learning. Semi-structured interviews were conducted with 50 students invited based on a maximum variation strategy. Based on the thematic analyses undertaken, four themes (i.e., programme delivery, linguistic improvement, learning transfer and change in self-efficacy) were identified and discussed. These themes contributed to the formulation of SILVER, an innovative framework of components for consideration in EAP course design and delivery within higher education.